2017
DOI: 10.1016/j.ajhg.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Penetrance of Polygenic Obesity Susceptibility Loci across the Body Mass Index Distribution

Abstract: A growing number of single-nucleotide polymorphisms (SNPs) have been associated with body mass index (BMI) and obesity, but whether the effects of these obesity-susceptibility loci are uniform across the BMI distribution remains unclear. We studied the effects of 37 BMI-associated SNPs in 75,230 adults of European ancestry across BMI percentiles by using conditional quantile regression (CQR) and meta-regression (MR) models. The effects of nine SNPs (24%)-rs1421085 (FTO; p = 8.69 × 10), rs6235 (PCSK1; p = 7.11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 87 publications
2
55
0
1
Order By: Relevance
“…Repeating our CQR-MR analyses for the variants most strongly associated with height identified by the GIANT consortium [45] revealed scant evidence for variants with nonuniform effect sizes across quantiles. This finding is consistent with previously-observed results for this trait [35,46]. Since height is known to have a very high narrow-sense heritability [45], our findings point to a lack of GxE or GxG interactions for height SNPs that have strong marginal associations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Repeating our CQR-MR analyses for the variants most strongly associated with height identified by the GIANT consortium [45] revealed scant evidence for variants with nonuniform effect sizes across quantiles. This finding is consistent with previously-observed results for this trait [35,46]. Since height is known to have a very high narrow-sense heritability [45], our findings point to a lack of GxE or GxG interactions for height SNPs that have strong marginal associations.…”
Section: Discussionsupporting
confidence: 93%
“…The detection of non-uniform genetic effect sizes across quantiles of the trait distribution by CQR-MR has previously been proposed as a method for identifying SNPs involved in GxE or GxG interactions, without any prior knowledge of the identity of the interacting variant or environmental exposure [35]. Here, we studied changes in genetic effect size across the refractive error trait distribution in SNPs previously shown to be associated with this trait, and found evidence for non-uniform effects in 88% of the 146 variants tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although often difficult in practice, replication studies should ideally use protocols with antipsychotic monotherapy, especially for children and adolescents in their first psychotic episode, and, like our study, ideally commence data collection when patients are antipsychotic-naïve. Additionally, extending the analysis to other antipsychotics and to more genes, as well as conducting more complex analyses including consideration of gene-environment interactions including epigenetics and gene-gene interactions models, could shed further light on relevant biological mechanisms [39]. As patients and their caregivers are certainly interested in preventing and ameliorating antipsychotic-associated weight gain and predicting who will respond well to interventions for this and who will not, further collaborative research efforts in this area are indicated.…”
Section: Resultsmentioning
confidence: 99%
“…To date, GWA analyses have identified more than thirty susceptibility loci robustly associated with obesity measured by body mass index (BMI). Those loci are in or near genes, including GNPDA2, SH2B1, TMEM18, MTCH2, CDKAL1, FAIM2, and MC4R [5][6][7][8]. It has been reported that the genotype-phenotype association varies in diverse groups of patients, and results need to be verified in a specific population [9].…”
Section: Introductionmentioning
confidence: 99%